(untitled) (Revista Linhas, 2007)
Os movimentos sociais surdos no Brasil e no mundo têm questionado a visão homogeneizada das sociedades e reivindicam uma política de reconhecimento quanto as suas diferenças. A educação escolar dos surdos é um exemplo. Esse artigo se propõe a tecer comentários de natureza teórica e metodológica implicados numa proposta de educação bilíngüe para surdos, aproximando-se de reivindicações pleiteadas há longo tempo e sistematizadas nos últimos anos, juntamente com os movimentos sociais surdos de Santa Catarina. Palavras-chave: Movimentos sociais surdos. Educação bilíngüe. Proposta de educação em Santa Catarina. E Social movements of the deaf in Brazil and throughout the world have been questioning the homogenized perspective of societies and demanding a policy of recognition of their differences. Schooling for the deaf is one example. This article presents commentaries of a theoretical and methodological nature concerning a proposal for bilingual education for the deaf. It is related to the requests made for many years - systematized in recent years - by social movements of the deaf in Santa Catarina State. Key words: Social movements of the deaf. Bilingual education. Educational proposal in Santa Catarina.